Introduction on Data Warehouse with OLTP and OLAP (International Journal of Engineering and Computer Science, 2017)
Data warehouse, online transaction processing system (OLTP) and on-line analytical processing (OLAP) are basically main need of the database collection in business, corporate fields and many areas. Nowadays many services, products and new techniques are available and offering many ideas in the DBMS. This paper is research about the data warehousing with OLAP and OLTP with the basic need and main parts of the business database management. The main here consider that Data warehouse usage, process, Data warehouse with Meta data, online transaction processing system (OLTP), on-line analytical processing (OLAP) and also OLTP vs. OLAP with advantages and disadvantages